Economic equity among ethnic in retail sector: case study in Seremban City Center, Negeri Sembilan - Siti Umira Sulaiman; J. J. Lajuni; Shaharudin Idrus; Abdul Samad Hadi (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Retail sector is one of important components in urban economic activity for urban livability. Currently, the retail sector contributes 60% of Malaysia’s Gross Domestic Product (GDP). Since retail sector provide more than half of the country’s GDP, an in-depth study to understand the framework of this sector should be emphasized. This paper will discuss the participation of Bumiputera in the retail sector with a focus on the Seremban City Center (SCC) as the designated study area. The purpose of this paper is to examine whether the New Economic Policy (NEP) is successful in bringing about even economic equity by ensuring 30% Bumiputera participation in retail sectors. Preliminary results obtained through primary and secondary data indicates that Bumiputera involvement is only 7% (Malays), while 93% of it is participated by non Bumiputera (Indian 13% and Chinese 80%). Bumiputera only involved in specific business such as restaurant, beauty care, travel and insurance agency, tuition center, boutique and also private clinics. In addition, data trend for the past three decades showed a mere 6% increased in Bumiputera participation in retail sector in SCC. This paper discusses the important of the retail activities for urban dwelling. The preliminary result shows that participation of the Bumiputera in retail sector are still questionable and urban planner should play more roles for the Bumiputera livability and sustainability.